Pengaruh Pijat Bayi Terhadap Perkembangan Motorik Anak Usia 0-2 Tahun : Literatur Review - Finka Novia Rahmadani; Kamelia Ananditha; Lutfi Dwy Adinda; Teresia Suminta Rotua Situmorang (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
Infant massage is one of the nonpharmacological interventions that has been proven effective in supporting early childhood motor development. This study aims to analyze the impact of infant massage on gross and fine motor development in children aged 0-2 years based on a literature review of eight scientific journals. The results showed that infant massage significantly contributed to the improvement of body weight, muscle strength, movement coordination, and visual-motor integration. In addition, there is a positive relationship between early motor development and cognitive abilities, including memory, verbal and quantitative abilities. Environmental factors, such as parental education and the quality of stimulation at home, also influence the effectiveness of infant massage. However, there are some research gaps regarding the socioeconomic and long-term effects of infant massage on child development. Therefore, further research with more robust experimental designs is needed to comprehensively explore the impact of infant massage. These findings emphasize the importance of infant massage as a simple, effective, and applicable method of early stimulation to support optimal child development.